1994
DOI: 10.1099/0022-1317-75-6-1491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of M and N gene sequences distinguishes variation amongst equine arteritis virus isolates

Abstract: cDNA copies of the M and N genes of equine arteritis virus (EAV) isolates were synthesized by reverse transcription followed by polymerase chain reaction amplification. The cDNA was subjected to a cycle sequencing strategy using Taq polymerase, and the nucleotide and derived amino acid sequences of 10 virus isolates were compared. The M and N genes of all isolates had the same initiation and termination sites as the prototype

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
5
33
2
Order By: Relevance
“…Complement fixation (Fukunaga & McCollum, 1977) and cross-neutralization studies using monovalent equine antisera in homologous and heterologous virus neutralization tests (Fukunaga et al, 1994) have indicated that minor antigenic variation between EAV isolates does exist. At the genetic level, RNase T1 oligonucleotide fingerprinting of viral genomes (Murphy et al, 1988) and sequence analysis of EAV M and N genes from different isolates (Chirnside et al, 1994) have also demonstrated the existence of variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement fixation (Fukunaga & McCollum, 1977) and cross-neutralization studies using monovalent equine antisera in homologous and heterologous virus neutralization tests (Fukunaga et al, 1994) have indicated that minor antigenic variation between EAV isolates does exist. At the genetic level, RNase T1 oligonucleotide fingerprinting of viral genomes (Murphy et al, 1988) and sequence analysis of EAV M and N genes from different isolates (Chirnside et al, 1994) have also demonstrated the existence of variation.…”
Section: Discussionmentioning
confidence: 99%
“…EAV G L is a heterogeneously glycosylated envelope protein responsible for the characteristic 30-42 kDa smear seen upon analysis of virus proteins in polyacrylamide gels (van Berlo et al, 1986;de Vries et al, 1992) Minor antigenic differences between EAV isolates have been demonstrated in serological studies (Fukunaga & McCollum, 1977;Fukunaga et al, 1994). Additionally, limited genomic variation was observed by RNase T1 fingerprinting (Murphy et al, 1988(Murphy et al, , 1992, although sequencing studies have revealed that the EAV M and N proteins are highly conserved between isolates (Chirnside et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Minor antigenic differences among isolates have been detected using polyclonal antiserum (Fukunaga & McCollum, 1977) and oligonucleotide fingerprint comparisons of genomic RNAs from geographically diverse isolates suggest that sequence differences may exceed 5% (Murphy et al, 1992). Direct comparison of the nucleotide sequences from the M and N genes of diverse isolates revealed differences of 3 % to 7 % within these two ORFs (Chirnside et al, 1994). However, correlation of antigenic differences with sequence differences or with biological phenotype has been hampered by the lack of more specific reagents.…”
Section: Introductionmentioning
confidence: 99%
“…I), [1,3,7,11,12,14,16]. These viruses, which were propagated in RK-13 cells using established procedures [17], varied in virulence, came from different geographical locations and had been isolated over a period of 30 years.…”
Section: Eav Isolatesmentioning
confidence: 99%